Underuse of reperfusion therapy with systemic thrombolysis in high-risk acute pulmonary embolism in a Portuguese center - Martinho, Mariana (2024)
© 2023 Sociedade Portuguesa de Cardiologia. Published by Elsevier España, S.L.U. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/)